"Desafios de uma Estudante Estagiária de Educação Física na implementação de estratégias de Desenvolvimento Positivo" - Marta Costa Ferreira (2021)
This document materializes in a practicum report within the scope of the school placement's Curricular Unit, it is one of the integral parts of the study plan for the 2nd cycle of studies on Physical Education Teaching in Basic and Secondary Education at the Faculty of Sports of the University of Porto. The school placement represents one of the most striking moments in a student's life, as it consists of the intervention process in a real context as a Physical Education teacher. The path taken in the school placement of a preservice teacher (the author) inserted in a group madewith four elements with particular and diversified characteristics is portrayed throughout the document. This work took place in a school located in Porto and was supervised by a faculty advisor and a supervisor from the school, which were essential elements for the proper functioning of the school placement. This experience was enriching in several domains, both on a personal and professional level about how to be a Physical Education teacher. The reflection on personal identity and the profession were the starting point of this document, with the aim of framing the concepts associated with the process that the preservice teacher would face in a real context. Thus, the reflection was on practices, perspectives, and conceptions. The evolution process of Physical Education teaching was particularly atypical, due to the pandemic on a worldwide scale, as the preservice teacher was exposed to several upheavals that she had to understand and overcome. The action-research study focused on positive youth development strategies allowed us to observe a positive evolution regarding respect and the relationship between students in the class and with the preservice teacher.